Advancing Through the Pandemic From the Perspective of Marine Graduate Researchers: Challenges, Solutions, and Opportunities - Pardo, Juan C. F.; Ramon, Debra; Stefanelli-Silva, Gabriel; Elegbede, Isa; Lima, Luciana S.; Principe, Silas C. (Frontiers in Marine Science, 2020)
The ongoing COVID-19 pandemic has brought about a new social and academic reality to researchers worldwide. The field of marine science, our own topic of interest, was also impacted in multiple ways, from cancellation of lab and field activities to postponement of onboard research. As doctoral/Ph.D. researchers, we have a time-sensitive academic path, and our current situation may constrain our academic future. At the same time, the pandemic demands revised strategies to deal with the ongoing difficulties and tackle similar future situations. In this perspective, we have gathered information on the challenges, solutions and opportunities for graduate researchers in the field of marine science by 1) discussing the relevant short and long term challenges caused by the pandemic, 2) providing feasible immediate and near-future solutions, 3) compiling opportunities (courses, scientific events, academic positions) and 4) creating a shared social media platform to make the available information on new opportunities more accessible. With this, we hope to add to the efforts to advance the academic career of marine graduates during this harsh period.